Monitoring of postoperative complications in the home environment - Alvaro Francisco Lopes de Sousa; Paula Regina de Souza Hermann; Inês Fronteira; Denise de Andrade (Rev Rene, 2020)
Objective: to propose a guideline for monitoring postoperative complications in patients in the home environment. Methods: research developed using the Delphi technique with 45 Brazilian health professionals. Google Forms were used for data collection and a Likert scale was used for consensus purposes. The data were analyzed using qualitative (content analysis) and quantitative (frequency and percentage analysis) techniques. Results: sixteen complications eligible to aid in the monitoring of surgical patients after discharge were listed, as well as signs and symptoms to be observed, and frequency and time of monitoring. According to the judges, surgical patients must be monitored at least once a day (68.8%). The maximum monitoring time varied from 48 hours to 30 days in case of risk of infection. Conclusion: the guideline is valid to be used to detect complications in surgical patients in the home environment and to anticipate the need for readmission.